Migrants' and refugees' health: towards an agenda of solutions - Stephen A. Matlin; Anneliese Depoux; Stefanie Schütte; Antoine Flahault; Luciano Saso (Frontiers Media S.A., 2018)
Abstract Despite the greatly increased numbers of migrants and refugees worldwide in recent years, insufficient attention has been paid to addressing their health needs. While a variety of international instruments assert the right to health, in practice, migrants and refugees-especially those awaiting clarification of their status, such as asylum seekers and those without documentation-often fall in cracks between service providers and humanitarian relief programmes at national and regional levels. This report provides a summary of the current state of knowledge regarding the health issues of migrants and refugees and of the extent to which they are being met. It highlights, through a series of case studies, the diverse approaches to policies, entitlements and services provided in different jurisdictions, ranging from regional (Europe) and country (Germany, Iran, Italy, Turkey, South Africa) levels to provinces and cities (Quebec/Montreal, Berlin). These provide evidence of successes and challenges and highlight areas requiring further effort, including in the domains of policy, service design and delivery, education and training, research and communication. They also underscore the challenges of highly neglected aspects such as mental health and the critical importance of developing cultural/transnational competence in the health professional individuals and institutions working with migrants and refugees. Results from discussions taking place in an M8 Alliance Expert Group Meeting (Rome, 23-24 June 2017) and from the literature are synthesised to develop an 'agenda of solutions'. This agenda aims to provide a comprehensive framework, which bridges humanitarian, ethical and rights-based imperatives to provide a framework for action to tackle this crucial area.